2016
DOI: 10.1167/iovs.16-19087
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell–Derived Photoreceptor Transplants Differentially Integrate Into Mouse Models of Cone-Rod Dystrophy

Abstract: Comparison of photoreceptor grafts in preclinical models with incomplete or complete photoreceptor loss, showed differential transplant success with effective and impaired integration, respectively. Thus, Cpfl1/Rho-/- mice represent a potential benchmark model resembling patients with severe retinal degeneration to optimize photoreceptor replacement therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 53 publications
1
65
0
1
Order By: Relevance
“…Tucker et al reported similar findings in a degenerative mouse model, where they showed that subretinal injection of mouse iPSC-derived photoreceptor precursors integrated into the retinal ONL and improved electroretinography responses (a measurement of lightmediated trans-retinal function across the whole retina) (Tucker et al, 2011). A recent mouse 3D retinal organoid study showed that transplanted organoid-derived photoreceptors can survive in the subretinal space and differentially integrate into the retina of mouse models with cone-rod degeneration (Santos-Ferreira et al, 2016). Interestingly, effective or poor integration was observed in mice with incomplete or complete photoreceptor loss, respectively, indicating that the stage of disease progression has an impact on cell integration.…”
Section: Rp and Photoreceptor Transplantationmentioning
confidence: 80%
“…Tucker et al reported similar findings in a degenerative mouse model, where they showed that subretinal injection of mouse iPSC-derived photoreceptor precursors integrated into the retinal ONL and improved electroretinography responses (a measurement of lightmediated trans-retinal function across the whole retina) (Tucker et al, 2011). A recent mouse 3D retinal organoid study showed that transplanted organoid-derived photoreceptors can survive in the subretinal space and differentially integrate into the retina of mouse models with cone-rod degeneration (Santos-Ferreira et al, 2016). Interestingly, effective or poor integration was observed in mice with incomplete or complete photoreceptor loss, respectively, indicating that the stage of disease progression has an impact on cell integration.…”
Section: Rp and Photoreceptor Transplantationmentioning
confidence: 80%
“…These retinal organoids continue to develop into an optic cup and subsequently pseudo-stratified retinal tissue (Eiraku et al, 2011; Nakano et al, 2012). Retinal organoid technology has become a widely used method to generate transplantable photoreceptors as demonstrated by several studies (Gonzalez-Cordero et al, 2013; Assawachananont et al, 2014; Decembrini et al, 2014; Santos-Ferreira et al, 2016b). Transplantation of retinal organoid-derived photoreceptors showed similar results to grafted primary photoreceptors.…”
Section: Transplantation Of Donor Photoreceptors Derived From Pluripomentioning
confidence: 99%
“…With great interest, we read the article ''Stem Cell-Derived Photoreceptor Transplants Differentially Integrate Into Mouse Models of Cone-Rod Dystrophy'' by Santos-Ferreira et al, 1 recently published in Investigative Ophthalmology and Visual Science. It's exciting to see that retinal degeneration can be rescued by photoreceptor transplantation in this study.…”
mentioning
confidence: 99%